Efektivitas Metode Dikte Untuk Meningkatkan Keterampilan Menulis Siswa - M. Abrar Putra Kaya Harahap; Adil Rosyadi Hasibuan; Aviva Hanum Siregar; Sabina Khairunnisa; Nur Hasanah Ramadhani (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This study aims to use dictation to improve students' listening skills in Indonesian and to determine the effectiveness of dictation in improving students' listening skills in descriptive texts. This research is a collective action research. This research uses the dictation method to improve the skills of listening to descriptive texts in Indonesian subjects. Action research for this course consists of 2 cycles. Each cycle consists of four stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the classroom action research showed that students' listening skills improved by using the dictation method. Dictation is a method commonly used to measure students' writing ability. With dictation, students must be able to understand the meaning of what they hear and then write it down while dealing with time constraints.In the end, using the dictation method can improve the writing skills of students in lower grades who initially could only write by looking at the writing on the blackboard or copying, now they are starting to be able to write slowly.